A metal-polyphenol network-based iron supplement with improved stability and reduced gastrointestinal toxicity for iron deficiency anemia therapy - Ying Yao; Yuanzheng Chen; Jie Fu; Jinsong Ding; Wenhu Zhou; Xinyi Chen; Xiuping Wan (Materials Today Bio)
Iron deficiency anemia (IDA) is a global health concern, particularly affecting women and children of reproductive age. Although oral iron supplements are the standard treatment for IDA, their bioavailability is often compromised by food interactions, and they are associated with significant gastrointestinal side effects. To overcome these limitations, we developed a novel iron nano-supplement, TA-Fe NPs, based on metal-polyphenol networks (MPNs) formed through the coordination of tannic acid (TA) and Fe3+. These uniform nanoparticles (∼190 nm) offer enhanced chemical stability and reduced food interference compared to traditional iron supplements. The polyphenolic TA component provides antioxidant properties, effectively mitigating oxidative stress and inflammation induced by free iron ions. To further improve stability and intestinal absorption, TA-Fe NPs were encapsulated in an enteric coating (TA-Fe@L100) to protect against acidic conditions in the stomach. In a mouse model of IDA, TA-Fe@L100 demonstrated superior therapeutic efficacy compared to FeSO4, including improvements in hematological parameters, organ iron storage, and gut microbiota balance. Importantly, TA-Fe@L100 alleviated common gastrointestinal side effects associated with iron supplementation, presenting a promising alternative for IDA treatment. Our findings suggest that TA-Fe@L100 is a cost-effective and biocompatible oral iron supplement with minimal side effects, offering significant potential for broader clinical application in the management of IDA.